Evaluating China's integration in world trade with a gravity model based benchmark - Matthieu Bussière; Bernd Schnatz (European Central Bank (ECB), 2006)
The rapid transition of China from a closed agricultural society to an industrial powerhouse has been associated with a rapid increase in the share of China in world trade. As the world is taking the full measure of this phenomenon, tensions have been arising ranging from holding China partly responsible for global imbalances to complaints about the “excessive” competitiveness of Chinese products. Without a quantifiable benchmark, however, such claims are difficult to judge. This paper therefore provides an assessment of China's “natural” place in the world economy based on a new set of trade integration indicators. These indicators are used as a benchmark in order to examine whether China's share in international trade is consistent with fundamentals such as economic size, location and other relevant factors. They constitute a better measure of trade integration that incorporates many more factors than traditional openness ratios. Results show that the model tracks international trade well and confirm that China is already well integrated in world markets, particularly with North America, several Latin American and East Asian emerging markets and most euro area countries.
Keywords: C23; F15; F14; 330; China; Gravity Model; panel data; Trade; Internationale Wirtschaftsbeziehungen; Internationale Arbeitsteilung; Globalisierung; Gravitationsmodell; China